Analysis of synchronized charge extraction for piezoelectric energy harvesting - Tang, Lihua (2014)
In the past few years, various power conditioning circuits have been proposed to improve the efficiency of piezoelectric energy harvesting, among which the synchronized charge extraction (SCE) technique has been enthusiastically pursued. In the literature, the SCE technique is investigated based on the uncoupled or in-phase assumptions. The uncoupled assumption is only valid for weak electromechanical coupling and the in-phase assumption is not applicable for energy harvesting at off-resonance. In this paper, we derive an accurate analytical solution for the piezoelectric energy harvesting systems with the SCE technique. Based on this solution, we investigate the applicability of the SCE technique for different cases, i.e. the piezoelectric energy harvester (PEH) with various degrees of electromechanical coupling and the PEH excited at various frequencies. Circuit simulation is also conducted with an accurate circuit model derived for PEHs and the results validate the analytical outcomes. Both the accurate analytical solution and the circuit simulation show that the SCE technique cannot improve or even reduces the power output at resonance if the coupling of the PEH is not negligible. The SCE technique is found capable of significantly boosting the efficiency of energy harvesting only for the PEH vibrating at off-resonance frequencies or with weak coupling.